2012
DOI: 10.1042/bj20120245
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin biosynthesis and its regulation

Abstract: The GAs (gibberellins) comprise a large group of diterpenoid carboxylic acids that are ubiquitous in higher plants, in which certain members function as endogenous growth regulators, promoting organ expansion and developmental changes. These compounds are also produced by some species of lower plants, fungi and bacteria, although, in contrast to higher plants, the function of GAs in these organisms has only recently been investigated and is still unclear. In higher plants, GAs are synthesized by the action of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
573
0
14

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 702 publications
(628 citation statements)
references
References 203 publications
23
573
0
14
Order By: Relevance
“…Consistent with earlier results that genes encoding DELLA proteins are feed-forward regulated by GA Hedden and Thomas, 2012), we found that Fv GAI was upregulated in Fv SOC1 overexpression plants compared with SD strawberry and, again, that the response was opposite in the RNAi line (see Supplemental Figure 15 online). Strawberry homologs of positive regulators of GA signaling, GIBBERELLIN INSENSITIVE DWARF1 and SLEEPY (Harberd et al, 2009), were not clearly affected in transgenic lines (see Supplemental Figure 15 online).…”
Section: Fv Soc1 Activates Ga Biosynthesissupporting
confidence: 80%
“…Consistent with earlier results that genes encoding DELLA proteins are feed-forward regulated by GA Hedden and Thomas, 2012), we found that Fv GAI was upregulated in Fv SOC1 overexpression plants compared with SD strawberry and, again, that the response was opposite in the RNAi line (see Supplemental Figure 15 online). Strawberry homologs of positive regulators of GA signaling, GIBBERELLIN INSENSITIVE DWARF1 and SLEEPY (Harberd et al, 2009), were not clearly affected in transgenic lines (see Supplemental Figure 15 online).…”
Section: Fv Soc1 Activates Ga Biosynthesissupporting
confidence: 80%
“…Biosynthesis of GA 12 , the common precursor for all GAs in plants, is catalyzed by ent-kaurene oxidase (KO) and ent-kaurenoic acid oxidase (KAO) (34). The GA 12 content was strongly increased in E17 seeds as compared with WT (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, only KAO2-but not KAO1-expression is affected by DOG1 overexpression (SI Appendix, Fig. S9), indicating that different mechanisms are involved in the regulation of these two genes, as has been shown for duplicated KAO genes in pea and sunflower (34). KO expression is directly regulated by the bZIP transcription factor REPRESSION OF SHOOT GROWTH (RSG) (39), which also has been suggested to regulate KAO expression (40).…”
Section: Dog1 Determines the Temperature Window For Germination By Rementioning
confidence: 99%
“…6A). Then, we used quantitative reverse transcription (RT)-PCR to measure the expression levels of the four genes of GA 3-oxidases and the five genes of GA 20-oxidases in Arabidopsis, whose induction could explain the high level of GA accumulated in the athb25-1D mutant (Hedden and Thomas, 2012). The expression levels of GA3OX1 and GA3OX3 were below detection, but we found a 2.5-fold induction of GA3OX2 in this mutant (Fig.…”
Section: Ga-dependent Phenotypes In Athb25-overexpressing Linesmentioning
confidence: 99%